Ayurvedic Management of Adenoid Hypertrophy in Children - Arun B; Athira S (International Journal of Ayurveda and Pharma Research, 2025)
Upper airway obstruction in children remains a concern and one of the most common causes is attributed to adenoid hypertrophy is the reason. The cause is mostly attributed to an increased response to immunologic activity. The prevalence in children has been estimated at 34.5%. The clinical manifestation of adenoid hypertrophy is varied in children and can be accompanied by various comorbidities. Upper airway obstruction usually leads to mouth breathing, nasal diseases, asthma and other symptoms. If not managed properly it can lead to serious conditions like sleep apnea, cognitive impairment and altered craniofacial growth. A relatively common management in the condition is adenoidectomy. Reluctance of common people to surgery necessities an alternative and novel non-surgical approach to deal this condition, in which Ayurveda can showcase its value. The disease Kanthashaluka is one of the seventeen diseases affecting the throat mentioned is Mukharoga prakarana (chapter on diseases of mouth). Adenoid hypertrophy and Kanthashaluka has similar clinical features and the basic diagnosis and line of management is based on Kanthasaluaka. This is a single case study of a 7 years 9 months old child with grade 4 adenoid hypertrophy managed with Ayurvedic medicines. The after endoscopy revealed grade 2 adenoid. Proper medicines based on the stage of condition following the basic principles in Kasa swasa chikitsa (treatment of respiratory disorders) and Kanta roga chikitsa (treatment of throat diseases) can provide an effective management in the condition.